Synthetic investigations towards the preparation of novel tetracycline antibiotics - Farrell, Jennifer (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
This research initially concerned itself with the synthesis of a dimeric compound of tetracycline antibiotics linked by a flexible tether. Tetracycline antibiotics have been in use since their discovery in the 1940s but widespread resistance has become a problem, limiting their clinical use. We propose that a dimeric compound of tetracycline antibiotics would be capable of circumventing the most ubiquitous resistance mechanism, the tetracycline efflux proteins. Tetracycline antibiotics minocycline and anhydrotetracycline were chosen for use in this study.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.